2023
DOI: 10.1021/acsapm.3c00246
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-Cross-Linked Polymers with Sulfur-Based Functionalities for the Prevention of Aging Effects in PIM-1 Mixed Matrix Membranes

Abstract: The instability of gas permeation rates over time in PIM-1-based membranes is one of the obstacles preventing the implementation of this technology on larger scales. The addition of porous materials to the PIM-1 matrix is a known process to reduce aging effects in PIM-1-based membranes. Many porous solids of various chemical natures have been tested, ranging from inorganic to inorganic–organic hybrids to completely organic materials. Here, we report on the synthesis of two hyper-cross-linked polymers (HCPs) ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 47 publications
(122 reference statements)
1
1
0
Order By: Relevance
“…However, its aging was much less pronounced, which could be inferred as resulting from its greater thickness slowing down film densification [ 28 ]. This indicates that the aging is only diffusivity (i.e., free volume) dependent, and, therefore, solubility should not be impacted by aging, which is consistent with observations from the literature [ 29 , 30 ]. This was verified by comparing the solubility of PIM-1_D obtained from both volumetric direct measurements and indirect calculation from permeation experiments.…”
Section: Resultssupporting
confidence: 90%
“…However, its aging was much less pronounced, which could be inferred as resulting from its greater thickness slowing down film densification [ 28 ]. This indicates that the aging is only diffusivity (i.e., free volume) dependent, and, therefore, solubility should not be impacted by aging, which is consistent with observations from the literature [ 29 , 30 ]. This was verified by comparing the solubility of PIM-1_D obtained from both volumetric direct measurements and indirect calculation from permeation experiments.…”
Section: Resultssupporting
confidence: 90%
“…Hou et al reported a CO 2 capture capacity and a CO 2 /N 2 selectivity of 3.3 mmol g –1 and 20.1, respectively, at 273 K using a carbonate-based HCP as the adsorbent . Begni and co-workers provided evidence regarding the function of PIMs in mitigating the aging effects of PIM-based mixed matrix membranes . Moreover, because of the presence of extensive π electrons, the HCPs are believed to adsorb aromatic organic molecules like organic dyes by π–π interaction.…”
Section: Introductionmentioning
confidence: 99%